The Effect of SSCS Learning Model with Summarizing Strategies on Grade IX Students’ Critical Thinking Skills in Biotechnology - Maria Esa; Yusnaeni; Mbing Maria Imakulata; Moses Kopong Tokan (Indonesian Journal of Biology Education, 2026)
Critical thinking skills are essential in the learning process. Previous research indicated that students’ critical thinking skills remained weak, highlighting the need for effective learning models and strategies. This study aims to determine the effect of the Search, Solve, Create, and Share (SSCS) learning model with a summarizing strategy on students' critical thinking skills in biotechnology material in grade IX at UPTD SMPN 19 Kupang in the 2025/2026 academic year.This study employed a quasi-experimental design with a non-equivalent control group involving two classes selected through purposive sampling. The instrument used was an essay test based on critical thinking indicators: providing simple explanations, developing basic skills, making inferences, giving further explanations, and planning strategies and tactics. Data were analyzed using a t-test in SPSS version 21. The results showed a significant effect of the SSCS model integrated with summarizing strategies on students' critical thinking skills (p < 0.05). The average score of the experimental class was 30.00, while the control class scored 19.39. These findings indicate that the SSCS learning model effectively improves students' critical thinking skills.